Maintenance of Steam Bottle Water to Keep Operational Auxiliary Steam Bottles on The Mv. Ile De Re - Salsabila Alattas, Syarifah; Simanjuntak, P. Dwikora; Suhartini, Capt.; Fahcruddin, Imam (International Journal of Advanced Multidisciplinary, 2023)
Various types of marine vessels require fuel to drive the main engine and auxiliary engines. The fuel requires hot steam as a heater so that the fuel reaches the appropriate temperature, not only fuel but hot steam is also needed for the accommodation space on the ship. The steam boiler is a closed vessel that can produce hot steam with a pressure greater than one atmosphere, to be able to produce hot steam, a heated medium is needed, namely fresh water. The water used in the steam generation process greatly affects the condition of the boiler. Therefore, the quality of water in the boiler must always be considered and maintained so that it is always in good condition, so that the boiler will always be in prime condition. In reality, steam boilers often experience disturbances, such as on the MV. ILE DE RE there is a decrease in the quality of boiler water and the occurrence of scale in the boiler. In this case, the research used an observation research method on boiler water by testing boiler water and it was found that the quality of boiler water was not up to standard with low pH levels up to 6.8, high alkalinity and high chloride up to 200 ppm. there is also a scale formation on the boiler water pipe which can be seen from the dirty condition of the boiler water when taken.